1998
DOI: 10.1037/h0089946
|View full text |Cite
|
Sign up to set email alerts
|

A one year experience in the use of Balint groups with third year medical students.

Abstract: Balint groups have been used to teach about the doctor-patient relationship at the postgraduate level, but their exclusive use with medical students has not been reported in the United States. This article reports on a time limited Balint group experience with third year medical students during the family medicine clerkship rotations spanning a full academic year. Overall, the experience was appreciated by the students. Despite their limited clinical experience, students participated well and they discussed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 6 publications
2
25
1
Order By: Relevance
“…The overall quality of evidence was mixed (Table 2). Three out of four of the quantitative studies were found to be at high risk of bias (Brazeau et al 1998;Yakeley et al 2011;Parker & Leggett 2012). The non-randomised controlled trial was judged to have a low risk of bias for the majority of domains but lacked information about missing outcome data (Airagnes et al 2014).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall quality of evidence was mixed (Table 2). Three out of four of the quantitative studies were found to be at high risk of bias (Brazeau et al 1998;Yakeley et al 2011;Parker & Leggett 2012). The non-randomised controlled trial was judged to have a low risk of bias for the majority of domains but lacked information about missing outcome data (Airagnes et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Qualitative and quantitative evidence of mixed quality suggests that 'therapeutic alliance' is influenced by Balint group participation. All except two studies (Brazeau et al 1998;Parker & Leggett 2014) measured at least one outcome or theme mapping to 'therapeutic alliance' (see last section for the findings of one study). A non-validated questionnaire reported a statistically significant between-group difference in 'empathic approach' (n=163; p=0.03; no CI or effect size reported) but not the 'empathic concern' dimension of the IRI (Airagnes et al 2014).…”
Section: Therapeutic Alliancementioning
confidence: 99%
“…Balint groups have been used as a teaching method for medical students and have been reported in the literature in several countries, including Germany, 30 Italy, [31][32][33] South Africa, 34 Poland, 35 Finland 36 and the USA. 37 However, although Balint-style case discussion groups are now a compulsory part of the postgraduate curriculum for junior psychiatrists in the UK, to our knowledge there have been no published reports of Balint groups for medical students in the UK since Balint himself experimented with medical student discussion groups at UCL. 27 Although the aim of both interventions is to teach the student about the doctor-patient relationship, inevitably the students doing the SPS will learn a lot about psychodynamic psychotherapy, whereas in the SPS and the Balint groups the students will have contact with psychiatrists supervising their patients or running the Balint group.…”
Section: Implementing Psychotherapy Teaching Methods On a Wider Scalementioning
confidence: 99%
“…Reflections could take the form of letters to patients or could be focused on specific clinical situations that students often mention as challenging, such as bias [36]. The opportunity to reflect alone [37] and in peer groups [38] allows students to normalize their emotions and may allow students to develop a tolerance not only to their own imperfections, but also to their patients' imperfections [37,39]. Through repetitive reflection, students can develop narrative competence [21].…”
Section: Discussionmentioning
confidence: 99%